Autonomy, Consent, and the "Nonideal" Case. Issue 3 (7th April 2020) - Lillehammer, Hallvard
Abstract: According to one influential view, requirements to elicit consent for medical interventions and other interactions gain their rationale from the respect we owe to each other as autonomous, or self-governing, rational agents. Yet, the popular presumption that consent has a central role to play in legitimate intervention extends beyond the domain of cases where autonomous agency is present to cases where far from fully autonomous agents make choices that, as likely as not, are going to be against their own best interest. The question of how we should understand the rationale for eliciting consent in this range of "nonideal" cases is comparatively ill understood. In this paper, I explore the prospects of accounting for consent requirements in such "nonideal" cases by appealing to a set of agency-based interests, including an interest in playing a meaningful part in joint decisions affecting ourselves and others.